2009
DOI: 10.1007/bf03086278
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of bosentan in inoperable chronic thromboembolic pulmonary hypertension

Abstract: Background. Inoperable chronic thromboembolic pulmonary hypertension (CTEPH) is associated with a poor survival. Objectives. To evaluate the long-term response to a dual endothelin receptor antagonist in patients with inoperable CTEPH. Methods. All consecutive 18 patients (mean age 63±14 years) treated with bosentan for symptomatic inoperable CTEPH were included. Efficacy was evaluated by the log value of serum levels of N-terminal-pro brain natriuretic peptide (log NTpro BNP), New York Heart Association funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a second study, 77 patients treated with bosentan for >2 years in Japan experienced significant decreases in PVR [53]. In a third study, in the Netherlands, >2 years of bosentan treatment led to stable NYHA-FC levels, but 6MWD had decreased slightly from the improved short-term value (although not to baseline levels) [52]. Finally, a report from a single centre in Japan demonstrated better long-term survival in patients with CTEPH receiving bosentan, or other "modern treatment" (bosentan, sildenafil and new oral drugs being trialled), than those taking conventional therapy for CTEPH (5-year survival 89% versus 60%, p=0.047) [63].…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 92%
“…In a second study, 77 patients treated with bosentan for >2 years in Japan experienced significant decreases in PVR [53]. In a third study, in the Netherlands, >2 years of bosentan treatment led to stable NYHA-FC levels, but 6MWD had decreased slightly from the improved short-term value (although not to baseline levels) [52]. Finally, a report from a single centre in Japan demonstrated better long-term survival in patients with CTEPH receiving bosentan, or other "modern treatment" (bosentan, sildenafil and new oral drugs being trialled), than those taking conventional therapy for CTEPH (5-year survival 89% versus 60%, p=0.047) [63].…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 92%
“…The study demonstrated a positive treatment effect of bosentan on hemodynamics over placebo in this patient population during follow-up of 16 weeks [13]. Other studies report 1 year survival rates of 95% in patients with inoperable CTEPH treated with bosentan [10,12].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, approximately 10% of patients who undergo PEA obtain no relief and maintain a pulmonary hypertensive state [7]. Modern specific pulmonary vasoactive medication (i.e., endothelin receptor antagonists, phosphodiesterase type 5 inhibitors, and prostacyclins) seems to improve the functional status and hemodynamics in patients with inoperable CTEPH at short-term follow-up [8][9][10][11][12][13][14][15][16][17]. However, limited data are available concerning the survival rate and time to clinical worsening in this patient population since those modern vasoactive treatments mentioned above were introduced.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to ERAs, we found that bosentan was associated with the highest probability for lowering BNP/NT-proBNP; this was the only drug that showed significant improvement in this parameter. However, retrospective research has identified that the long-term efficacy of bosentan failed to remain statistically significant in inoperable CTEPH patients [ 34 ]. Our results are based on RCTs and are not completely consistent with other published research.…”
Section: Discussionmentioning
confidence: 99%